PENGARUH PENGGUNAAN LULUR PEPAYA (CARICA PAPAYA L) TERHADAP PENCERAHAN KULIT BADAN - Angraini, Leni; Rostamailis, Rostamailis; Minerva, Prima (Journal of Home Economics and Tourism, 2015)
This study aims to analyze the effect of the use of papaya scrub to enlightenment body and smooth skin (skin of hands). This research is pre-experiment with one-group pretest-posttest design. The object of this research is the skin of hands has been changed into a dark, while the sample is a student of Education Makeup and Beauty Faculty of Engineering Department of Padang State University aged 21-25 years as many as five peoples and indicated to have dark hand skin condition. Sampling was done by purposive sampling technique conducted volunteers (voluntary). Assessment was conducted before treatment (pretest) and after treatment (posttest) with treatment 1 time in 15 days for about 6 times treatment. Data were analyzed using t-test analysis. The results showed that the use of herbal papaya for skin lightening hands after usage frequency papaya scrub 1 time in 15 days showed a significant effect of each indicator with the t arithmetic (14 840)> t table (2776) to change the color of the skin. As for the smoothness found changes for each indicator by using the t arithmetic (16,804). Each indicator followed by t test showed the difference between pretest to posttest significantly. This means that the use of herbal papaya against enlightenment and smoothness hands with a frequency of 1 time in 15 days showed significant results.Keyword: Scrub, papaya (Carica papaya L), treatment, skin, body (hands).